Potentiation of testicular cytotoxicity by the alkyltransferase inhibitor O6 benzylguanine and the 5-fluorouracil/N-(2-chloroethyl)-N-nitrosourea molecular combination, B.4152 - Thompson, Michael J.; Abdul Rahman, Suzanah; Baker, Theresa G.; Bibby, Michael Charles (Elsevier, 1996)
Alkylating agents are a group of compounds that have a cytotoxic effect due to their ability to form adducts with DNA. Cells possess the ability to repair this damage via an enzyme, O6-alkylguanine-DNA alkyltransferase (AGT). To study the effect of inhibiting this repair mechanism upon testicular cytotoxicity in BALB/c mice, the AGT inhibitor O6 benzylguanine (O6BG) was used in conjunction with the potential anticancer drug previous termB.4152next term. Paraffin sections were stained and examined using Chalkley scoring to identify the cells affected by the treatment. Using previous termB.4152next term alone the maximal effect upon the spermatogenic tissue was found to be after 32 days. The damage found was minor, with the spermatocytes and spermatids most affected. Using this time point it was found that the combined treatment produced widespread damage, with significant depletion of the majority of spermatogenic cell types. These results therefore indicate that differentiating spermatogenic cells are normally protected from previous termB.4152 induced damage by AGT, depletion of which significantly potentiates previous termB.4152 toxicity.